Effective removal of host cell-derived nucleic acids bound to hepatitis B core antigen virus-like particles by heparin chromatography - Valentic, Angela; Hubbuch, Jürgen (Frontiers in Bioengineering and Biotechnology, 2024)
Virus-like particles (VLPs) show considerable potential for a wide array of therapeutic applications, spanning from vaccines targeting infectious diseases to applications in cancer immunotherapy and drug delivery. In the context of hepatitis B core antigen (HBcAg) VLPs, a promising candidate for gene delivery approaches, the naturally occurring nucleic acid (NA) binding region is commonly utilized for effective binding of various types of therapeutic nucleic acids (NAther). During formation of the HBcAg VLPs, host cell-derived nucleic acids (NAhc) might be associated to the NA binding region, and are thus encapsulated into the VLPs. Following a VLP harvest, the NAhc need to be removed effectively before loading the VLP with NAther. Various techniques reported in literature for this NAhc removal, including enzymatic treatments, alkaline treatment, and lithium chloride precipitation, lack quantitative evidence of sufficient NAhc removal accompanied by a subsequent high VLP protein recovery. In this study, we present a novel heparin chromatography-based process for effective NAhc removal from HBcAg VLPs. Six HBcAg VLP constructs with varying lengths of the NA binding region and diverse NAhc loadings were subjected to evaluation. Process performance was thoroughly examined through NAhc removal and VLP protein recovery analyses. Hereby, reversed phase chromatography combined with UV/Vis spectroscopy, as well as silica spin column-based chromatography coupled with dye-based fluorescence assay were employed. Additionally, alternative process variants, comprising sulfate chromatography and additional nuclease treatments, were investigated. Comparative analyses were conducted with LiCl precipitation and alkaline treatment procedures to ascertain the efficacy of the newly developed chromatography-based methods. Results revealed the superior performance of the heparin chromatography procedure in achieving high NAhc removal and concurrent VLP protein recovery. Furthermore, nuanced relationships between NA binding region length and NAhc removal efficiency were elucidated. Hereby, the construct Cp157 surpassed the other constructs in the heparin process by demonstrating high NAhc removal and VLP protein recovery. Among the other process variants minimal performance variations were observed for the selected constructs Cp157 and Cp183. However, the heparin chromatography-based process consistently outperformed other methods, underscoring its superiority in NAhc removal and VLP protein recovery.